Fast online‐customized (FOCUS) parallel transmission pulses: A combination of universal pulses and individual optimization. Issue 6 (5th January 2021) - Herrler, Jürgen; Liebig, Patrick; Gumbrecht, Rene; Ritter, Dieter; Schmitter, Sebastian; Maier, Andreas; Schmidt, Manuel; Uder, Michael; Doerfler, Arnd; Nagel, Armin M.
Abstract : Purpose: To mitigate spatial flip angle (FA) variations under strict specific absorption rate (SAR) constraints for ultra‐high field MRI using a combination of universal parallel transmit (pTx) pulses and fast subject‐specific optimization. Methods: Data sets consisting of B0, B 1 + maps, and virtual observation point (VOP) data were acquired from 72 subjects (study groups of 48/12 healthy Europeans/Asians and 12 Europeans with pathological or incidental findings) using an 8Tx/32Rx head coil on a 7T whole‐body MR system. Combined optimization values (COV) were defined as combination of spiral‐nonselective (SPINS) trajectory parameters and an energy regularization weight. A set of COV was optimized universally by simulating the individual RF pulse optimizations of 12 training data sets (healthy Europeans). Subsequently, corresponding universal pulses (UPs) were calculated. Using COV and UPs, individually optimized pulses (IOPs) were calculated during the sequence preparation phase (maximum 15 s). Two different UPs and IOPs were evaluated by calculating their normalized root‐mean‐square error (NRMSE) of the FA and SAR in simulations of all data sets. Seven additional subjects were examined using an MPRAGE sequence that uses the designed pTx excitation pulses and a conventional adiabatic inversion. Results: All pTx pulses resulted in decreased mean NRMSE compared to a circularly polarized (CP) pulse (CP = 28%, UPs = 17%, and IOPs = 12%). UPs and IOPs improved homogeneity for all subjects. Differences in NRMSE between study groups were much lower than differences between different pulse types. Conclusion: UPs can be used to generate fast online‐customized (FOCUS) pulses gaining lower NRMSE and/or lower SAR values. Abstract : Click here for author‐reader discussions